2004
DOI: 10.1002/acp.1063
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality and anxiety on the oral performance of Japanese speakers of English

Abstract: This study investigated the relationship between personality and anxiety characteristics of Japanese students and their oral performance in English. The participants were 73 native-speakers of Japanese who were studying English at various language schools in New Zealand. They were administered the Maudsley Personality Inventory, the Spielberger State Anxiety Inventory, and a story-retelling task which was scored in terms of oral fluency, accuracy, complexity, and global impression. Significant correlations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…Woodrow (2006) argued that second language speaking anxiety to be a significant predictor of oral achievement. Oya et al (2004) found that there was significant correlation between extraversion and global impression scores, and state anxiety and clause accuracy scores. In keeping with Liu & Huang (2011), who reported that there are two important affective variables, anxiety and motivation have been found to be highly correlated to second/foreign language acquisition.…”
Section: Previous Related Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Woodrow (2006) argued that second language speaking anxiety to be a significant predictor of oral achievement. Oya et al (2004) found that there was significant correlation between extraversion and global impression scores, and state anxiety and clause accuracy scores. In keeping with Liu & Huang (2011), who reported that there are two important affective variables, anxiety and motivation have been found to be highly correlated to second/foreign language acquisition.…”
Section: Previous Related Studiesmentioning
confidence: 91%
“…Numerous empirical studies have revealed that anxiety has relationship and influence on academic performance (Oya et al, 2004;Saito & Samimy, 1996;Young, 1986;& Vitasari et al, 2010). A range of factors was revealed to contribute to anxiety such as low English proficiency, lack of practice, personality, fear of making mistakes and being laughed at, competition, and lack of confidence (Liu, 2006).…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Toeko Oya (2004) explored the relation between personality and anxiety characteristic of Japanese students and their oral performance in English. Participants were 73 native speakers of Japanese who were studying English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, in this study, filled pauses did not significantly correlate with any of the factors examined, including those relating to language contact. And looking at previous studies on second language oral performance that have employed filled pauses as a measure of fluency [32,33] reveals that this measure has also failed to show correlations with assessments of personality and anxiety. It may therefore simply be the case that filled pauses is not a useful measure of speaking fluency.…”
Section: The Usefulness Of Vocabulary Knowledge: Having the Words To Saymentioning
confidence: 99%